Design considerations for a W-band Josephson junction travelling wave parametric amplifier - Navarro Montilla, J; Barbier, A; Driessen, EFC; Tan, B-K (2024)
Most Josephson junction Travelling Wave Parametric Amplifiers (JTWPAs) developed so far have been focused on operation below 20 GHz, primarily driven by the choice of the qubit resonance frequency used in quantum computation research. Consequently, there is a lack of effort to extend their operation to higher frequency ranges. However, millimetre (mm)- wave JTWPAs could offer potential significant advantages for astronomy, but their operation in this regime is largely unexplored. In this paper, we describe the design considerations for extending JTWPAs operation to the W-band range. We present two JTWPA designs, one with and one without phase matching elements, and we discuss the design methodology of both approaches, before showing their predicted performance respectively.